The Flow of Illicit Funds : A Case Study Approach to Anti-Money Laundering Compliance - Tucker, Ola M. (Book collections on Project MUSE., 2022)
"This is a handbook and primer for compliance professionals and students of financial crime. Unlike other money laundering books currently on the market, which focus on the implementation of an anti-money laundering (AML) program, this book examines the most common, modern-day methods used by criminals to launder money, through a review of recent, high-profile case studies"--